Prophylactic ilio-inguinal neurectomy following Lichtenstein tension free hernioplasty for inguinal hernia: a prospective study - Raj G., Preetham; A. L., Nagaraja; V., Surendran; Sharma, Abhilash; Shariff, Ibrahim; Kumar M., Anil (International Surgery Journal, 2019)
Background: The objective of the study was to evaluate effect of prophylactic ilio-inguinal neurectomy on incidence of chronic groin pain following the Lichtenstein tension free hernioplasty for inguinal hernia. Methods: This prospective study included male cases admitted with uncomplicated inguinal hernia. Patients were categorised into two groups: Group A: Ilioinguinal nerve preserved, Group B: Ilioinguinal nerve excision. Standard tension-free Lichtenstein mesh repair was adopted. Patients were followed up for assessment of chronic groin pain, hypoesthesia, and numbness at post-operative day (POD) 3, POD14, 1 month and 3 months. Visual analog scale (VAS) was used to assess severity of pain. Sensory assessment was done using standard Semmes-Weinstein monofilament test. Student t test was used and a 2-sided p<0.05 was considered significant. Results: A total of 60 patients with uncomplicated inguinal hernia underwent Lichenstein mesh Hernioplasty (mean age of patients in nerve preservation: 35.8±11.9 years and nerve excision group: 42.7±9.6 years). Postoperative pain significantly decreased in group B at POD 3 (65.5% vs. 89.7%, p=0.01) and 3 months (0% vs. 24.1%, p=0.003) when compared to group A. Prevalence of numbness reduced significantly in group A at 3 month (44.8% vs. 86.2%, p=0.001). Although post-operative hypo aesthesia was comparable between the groups at POD 3 (84.6% vs. 78.1%), it decreased significantly in group A at 3 months (27.6 % vs. 86.2%, p<0.001) when compared to group B. Conclusions: Prophylactic excision of ilio-inguinal nerve during Lichtenstein mesh hernia repair decreases the incidence of chronic groin pain after surgery, without additional morbidities.